2010
DOI: 10.3109/09273971003758388
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Strabismus in Patients with Chronic Progressive External Ophthalmoplegia

Abstract: In selected patients with CPEO and exotropia, maximal bilateral surgery significantly improves ocular alignment and may relieve symptoms of diplopia, but due to the progressive nature of the disease, strabismus often recurs. Toxin can be invaluable in maintaining a satisfactory ocular alignment in patients with residual or progressive exotropias, who have undergone maximal horizontal rectus muscle surgery or multiple previous strabismus procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Should the eye become anchored in a grossly eccentric position, then muscle surgery to straighten it may be justified and beneficial but there is a risk of recurrence as the disease progresses (Tinley et al 2010). The eyes are relatively immobile in the later stages and prisms are then of little benefit.…”
Section: Managementmentioning
confidence: 83%
“…Should the eye become anchored in a grossly eccentric position, then muscle surgery to straighten it may be justified and beneficial but there is a risk of recurrence as the disease progresses (Tinley et al 2010). The eyes are relatively immobile in the later stages and prisms are then of little benefit.…”
Section: Managementmentioning
confidence: 83%
“…Seven of 13 patients with a manifest deviation showed diplopia. Tinley et al (2010) reported 25 CPEO patients including exophoria or exotropia with/without vertical deviation in 22 patients (88%). The remaining three patients showed esotropia, esotropia with vertical deviation and hypertropia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic progressive external ophthalmoplegia (CPEO) features slowly progressive external ophthalmoplegia and ptosis (Hansen & Logan 1966; Sorkin et al 1997; Wallace et al 1997; Moon‐Woo et al 2005; Richardson et al 2005; Hwang et al 2009; Tinley et al 2010; Chatzistefanou et al 2018). Its diagnosis could be made by muscle biopsy showing ragged‐red fibres or molecular genetic tests confirming mitochondrial abnormalities (Hansen & Logan 1966; Sorkin et al 1997; Wallace et al 1997; Moon‐Woo et al 2005; Richardson et al 2005; Hwang et al 2009; Tinley et al 2010; Chatzistefanou et al 2018). Patterns of strabismus in CPEO as well as ophthalmoplegia have been scarcely reported because of its rarity (Sorkin et al 1997; Wallace et al 1997; Richardson et al 2005; Hwang et al 2009; Tinley et al 2010; Chatzistefanou et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prisms can also be helpful for small residual angles, particularly as there is suggestion that CPEO patients can have narrower fusional amplitudes [ 18 ]. Botulinum toxin alone, although insufficient for the larger exodeviations seen in CPEO, may be particularly useful for residual angles that may develop post-surgically [ 19 , 20 ].…”
Section: Extraocular Manifestationsmentioning
confidence: 99%